2018
DOI: 10.3390/ma11030372
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Physico-Chemical Properties of Acryl-Coated Polypropylene Foils for Food Packaging by Reactive Particles from Oxygen Plasma

Abstract: This investigation was focused on the influence of long-living neutral reactive oxygen species on the physico-chemical properties of acryl-coated polypropylene foils for food packaging. Reactive species were formed by passing molecular oxygen through a microwave discharge and leaking it to a processing chamber of a volume of 30 L, which was pumped by a rotary pump. The density of neutral O-atoms in the chamber was tuned by adjustment of both the effective pumping speed and the oxygen leak rate. The O-atom dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The functionalization efficiency can be estimated from the measured density of neutral oxygen atoms in the plasma reactor and the surface of the polymer powder, taking into account the fluence needed for saturation of the polymer surface with oxygen functional groups from the available literature, i.e., 2 × 10 22 O-atoms/m 2 [ 19 , 20 ]. The required treatment time for receiving this fluence depends on the surface of all the powder particles Σ S powder , the surface of the stainless–steel dish S dish and the flux of O-atoms on the surface of the dish: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalization efficiency can be estimated from the measured density of neutral oxygen atoms in the plasma reactor and the surface of the polymer powder, taking into account the fluence needed for saturation of the polymer surface with oxygen functional groups from the available literature, i.e., 2 × 10 22 O-atoms/m 2 [ 19 , 20 ]. The required treatment time for receiving this fluence depends on the surface of all the powder particles Σ S powder , the surface of the stainless–steel dish S dish and the flux of O-atoms on the surface of the dish: …”
Section: Resultsmentioning
confidence: 99%
“…The lower limit of plasma functionalization of polymer powder is defined by the fluence of reactive species onto the treated samples. Unfortunately, there is no report on recommended fluences for saturation of polyethylene surfaces with polar functional groups, but Vukusic et al reported the optimal wettability of acryl-coated polypropylene foils after receiving the fluence of about 2 × 10 22 O-atoms/m 2 [ 19 ]. Similar numbers were also reported by Vesel et al for the case of polystyrene [ 20 ].…”
Section: Theoretical Limitationsmentioning
confidence: 99%
“…The formation of aldehyde and carboxyl groups may be seen from the high-resolution spectra. It is also known, that both plasma treatments yield higher roughness and increased surface free energy, which should enable better adhesion of coatings onto foils’ surfaces [ 40 , 41 , 42 , 43 ]. As already mentioned, ammonia plasma was meant to be done, whilst introduced amino groups can contribute to the antimicrobial activity, and oxygen plasma offers binding places for chitosan attachment onto foils’ surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Here we should note, that hydrogen and oxygen atoms are also lost by chemical reaction with the polymer surface. However, the surface is very quickly (in 1 s) saturated with functional groups and more steady state is obtained . The reaction of H or O atoms with the polymer surface may also results in products which have a lower reaction probability than the pristine polymer surface.…”
Section: Resultsmentioning
confidence: 99%
“…The density of atoms in the afterglow is not significantly lower than in glowing plasma so functionalization occurs in a short time. The density of O‐atoms on a smooth polymer surface which assures for saturation with polar groups upon treatment with O‐atoms in the afterglow is 10 19 –10 20 m −3 . The loss of atoms is either in the gas phase (predominantly at three body collisions) or on surfaces (by chemical reactions and heterogeneous surface recombination).…”
Section: Introductionmentioning
confidence: 99%